CONTENTS OF SOME MACRO- AND MICROELEMENTS IN CAREX HIRTA L. PLANTS ON THE TERRITORY OF THE BORYSLAV OIL FIELD - Цвилинюк, Ольга; Думич, Оксана; Джура, Наталья (SWorldJournal, 2020)
The article reveals the peculiarities of some macro-and microelements contents (N, P, K, Mg, Na, Fe, Zn, Mn, Cu) in Carex hirta L. plants, collected on the territory of the Boryslav oil field (Lviv region, Ukraine). Plant samples were taken from areas wit